Biostratinomy of the Ediacara Member (Rawnsley Quartzite, South Australia): implications for depositional environments, ecology and biology of Ediacara organisms. Issue 4 (6th August 2020) - Droser, Mary L.; Tarhan, Lidya G.; Evans, Scott D.; Surprenant, Rachel L.; Gehling, James G.
Abstract : The Precambrian Ediacara Biota—Earth's earliest fossil record of communities of macroscopic, multicellular organisms—provides critical insights into the emergence of complex life on our planet. Excavation and reconstruction of nearly 300 m 2 of fossiliferous bedding planes in the Ediacara Member of the Rawnsley Quartzite, at the National Heritage Ediacara fossil site Nilpena in South Australia, have permitted detailed study of the sedimentology, taphonomy and palaeoecology of Ediacara fossil assemblages. Characterization of Ediacara macrofossils and textured organic surfaces at the scale of facies, bedding planes and individual specimens has yielded unprecedented insight into the manner in which the palaeoenvironmental settings inhabited by Ediacara communities—particularly hydrodynamic conditions—influenced the aut- and synecology of Ediacara organisms, as well as the morphology and assemblage composition of Ediacara fossils. Here, we describe the manner in which environmental processes mediated the development of taphofacies hosting Ediacara fossil assemblages. Using two of the most common Ediacara Member fossils, Arborea and Dickinsonia, as examples, we delineate criteria that can be used to distinguish between ecological, environmental and biostratinomic signals and reconstruct how interactions between these processes have distinctively shaped the Ediacara fossil record.